2005
DOI: 10.1371/journal.pmed.0030003
|View full text |Cite
|
Sign up to set email alerts
|

Limits to Forecasting Precision for Outbreaks of Directly Transmitted Diseases

Abstract: BackgroundEarly warning systems for outbreaks of infectious diseases are an important application of the ecological theory of epidemics. A key variable predicted by early warning systems is the final outbreak size. However, for directly transmitted diseases, the stochastic contact process by which outbreaks develop entails fundamental limits to the precision with which the final size can be predicted.Methods and FindingsI studied how the expected final outbreak size and the coefficient of variation in the fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…A more intensive intervention (lasting for 6 days, versus 10 or 14 days) yielded slightly more averted cases than a longer intervention. Our results are also in agreement with a recent theoretical analysis, which found that the average outbreak size grew exponentially with the delay from the start of an outbreak to the implementation of an intervention, highlighting the importance of early intervention (Drake 2005).…”
Section: Discussionsupporting
confidence: 92%
“…A more intensive intervention (lasting for 6 days, versus 10 or 14 days) yielded slightly more averted cases than a longer intervention. Our results are also in agreement with a recent theoretical analysis, which found that the average outbreak size grew exponentially with the delay from the start of an outbreak to the implementation of an intervention, highlighting the importance of early intervention (Drake 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Since doubts have been raised in the literature about the use of final size data for emerging diseases (Drake, 2005), a simulation study was also performed to test identifiability, although a recent study by Blumberg and Lloyd-Smith (Blumberg and Lloyd-Smith, 2013) of joint identifiability of two parameters in a related model is also highly relevant in this context.…”
Section: Methodsmentioning
confidence: 99%
“…Our modelling approach which integrates presently available knowledge on RVF vector biology, is a first step towards the development of a climate-based early-warning system in Senegal which could allow prediction of at-risk periods for RVF, but certainly not the epidemic extent which is driven by human factors [54], [55].…”
Section: Discussionmentioning
confidence: 99%